Disruption of a binary organogel by the chemical warfare agent soman (GD) and common organophosphorus simulants. Issue 3 (28th November 2014) - Hiscock, Jennifer R.; Sambrook, Mark R.; Ede, Jayne A.; Wells, Neil J.; Gale, Philip A.
Abstract : The chemical warfare agent (CWA) soman (GD) acts as a molecular stimulus for the disruption of an anthracene-based binary organogel prepared in cyclohexane. Abstract : The chemical warfare agent (CWA) soman (GD) acts as a molecular stimulus for the disruption of an anthracene-based binary organogel prepared in cyclohexane. The CWA simulants dimethyl methylphosphonate (DMMP) and diethyl chlorophosphate (DCP) were also found to disrupt the binary organogel through changes in solvent polarity and reactions with the gelator.